Mutations in the thyroid transcription factor gene NKX2-1 result in decreased expression of SFTPB and SFTPC. (September 2018) - Attarian, Stephanie; Leibel, Sandra; Yang, Ping; Alfano, Danielle; Hackett, Brian; Cole, F; Hamvas, Aaron
Abstract Background Mutations in the NK2 homeobox 1 (NKX2-1 ) gene are associated with lung disease in infants and children. We hypothesize that disruption of normal surfactant gene expression with these mutations contributes to the respiratory phenotypes observed. Methods To assess transactivational activity, cotransfection of luciferase reporter vectors containing surfactant protein B or C (SFTPB orSFTPC ) promoters withNKX2-1 plasmids was performed and luciferase activity was measured. To assess the binding of mutated proteins to target DNA, electrophoretic mobility shift assays (EMSA) were performed using nuclear protein labeled with oligonucleotide probes representingNKX2-1 consensus binding sequences followed by gel electrophoresis. The effect of overexpression of wild-type (WT) and mutantNKX2-1 onSFTPB andSFTPC was evaluated with quantitative real-time PCR. Results Decreased transactivation of theSFTPB promoter by both mutants and decreased transactivation of theSFTPC promoter by the L197P mutation was observed. EMSA demonstrated decreased DNA binding of both mutations toNKX2-1 consensus binding sequences. Transfection of A549 cells withNKX2-1 expression vectors demonstrated decreased stimulation ofSFTPB andSFTPC expression by mutant proteins compared with that of WT. Conclusion Disruption of transcriptional activation of surfactant protein genes by these DNA-binding domain mutations is a plausible biological mechanism for disruption of surfactant function and subsequent respiratory distress.